Relação entre a cárie precoce da infância com o índice de Apgar e outros fatores de risco - Larquer, Ludiele Gonçalves Martins (2016)
The aim of this cross-sectional study was to investigate the association of early childhood caries (ECC) with the Apgar score (AS) and other variables related to the child (conditions at birth and medical history) and related to the child and parents and / or guardians and family (demographic, socioeconomic and behavioral). One hundred and twenty healthy children aged between 3-5 years-old treated by Pediatric Dentistry Area of Dentistry College of the Federal University of Uberlandia during 2015 were selected. To obtain qualitative and quantitative variables a questionnaire was applied as an interview to the parents and/or guardians. The 5-minute AS (interest exposure) was obtained through the record in the Child Health Handbook. To assess the prevalence of caries (clinical dependent variable), a single calibrated researcher conducted the clinical examination, according to the criteria of the World Health Organization. Caries experience was measured using the indexes dmft and dmfs. The children were classified into three groups, according to age and dmfs index: no caries (NC), with ECC and with severe early childhood caries (S-ECC). Data were tabulated and submitted to statistical analysis using the SPSS software (IBM, Inc, Chicago, Illinois, USA) 17th version. Three logistics models were carried out having the following classifications: NC and ECC, NC and S-ECC, ECC and S-ECC (p<0.05). The overall ECC prevalence, considering children with ECC and S-ECC, was 55,8% (n= 67). The AS was not a statistically significant variable. The child’s age, weaning age and recent hospitalization were variables associated with the ECC prevalence. The age of brush start and the educational level of the mother were variables associated with the S-ECC prevalence. Considering the ECC and the S-ECC groups, the child's age and the beginning of the use of fluoride toothpaste, recent hospitalization, the educational level of the mother and the father's income were associated with the S-ECC prevalence. Considering the methodology employed and the analysis of results, it was concluded that there was no association between the ECC with the AS in healthy children. However, an association was found of ECC and S-ECC with some variables related to birth and to medical history of the child (recent hospitalization), demographic (child’s age), socioeconomic (educational level of the mother and father's income) and behavioral (age of brush start, weaning age and use of fluoride toothpaste) related to children and to the parents and/or guardians.